The Combining Technique of Calculating the Sections of Reinforced Concrete Bending Elements Normal to its Longitudinal Axis, Based on the Deformation Model - Galinska, Tatyana; Ovsii, Dmytro; Ovsii, Mykola (International Journal of Engineering and Technology, 2018)
Methodical foundations for calculating the strength of normal sections of various types of steel-concrete bending elements are proposed, which allow calculating in dependence on the stress-strain state (SSS) at the moment of destruction of its components (concrete and structural reduced steel profile). The basis of the calculation allows solving two problems: the problem of determining the optimal section of reduced structural steel profile (RSSP), which reinforced the section of steel-concrete bending elements; the task of verifying the load-bearing capacity of a normal reduced section of various types of steel-concrete bending elements.Â Â